Regulation of deflationary stability of polissya agrolandscapes soil cover - Barvinskyi, A. (Land Management, Cadastre and Land Monitoring, 2017)
In the Ukrainian Polissya soil cover is dominated by sod-podzolic soils, that due tolight particle size distribution and relatively small amount of humus,  have weak aggregationand low resistance to deflation processes.Soil deflation here is often in the spring, when arable land have the lowest level of vegetation protection.Drywall southeast winds dry up much upper layers of soil, destroy its structure and cause local deflation, particularly in the areas of drained peat and mineral soils of sandyand sandy-loamygranulometric composition.Display of local deflation on the same land for several years, leading to significant loss of soil.The intensity of these hazards depends largely deflationary stability of the soil, of which the main criterion in the literature defined mechanical strength (cohesion) of soil aggregates and main indicator - content in soil aggregates with a diameter greater than 1 mm.Based on experimental data obtained in the Kyiv Polissya proven ability to adjust the deflationarydurability of sod-podzolic sandy-loamy soils by rational combining fertilizer plants and chemical reclamation.Increasing the strength of the structure at the joint application of lime and fertilizers due, based on a close correlation, positive changes in soil absorbing complex caused by calcium of lime and humus content increase and improve its quality composition: accumulationof calcium humates that play a leading role in grouting units. In addition, liming of unsaturated bases soils prevents the destruction and removal of these most valuable in agriculturally parts thereof: silt fraction.When applying lime on organo-mineral background of relative content increased by 8,2-18,4%, and the application of some fertilizers - on the contrary, decreased by 10,2%. Liming of acid soils increases the "grain rate structuring" at 0,3-0,6% compared to organo-mineral background, while the separate application of fertilizers reduces it to 2,1-2,7%.Comparison of granulometric and mikroagregative analysis by methodology of B.A.Nikitin shows that aggregation of large particles in the test soil occurs solely at the expense of sludge.In particular the use of mineral and organic fertilizer sludge fraction in the formation of a macrostructure does not participate (relative rate of participation of fines in the formation of macrostructure is 0). When combined fertilizer, the figure is 0,24-0,30 on unlimestoneareas and 0,30-0,48 on limestone plots.The process of aggregation in sod-podzolic sandy-loamy soil uneven: more (65-100%) in the intermediate fractions (0,25-0,001 mm) than in coarse (1-0,25 mm). When combined lime and fertilizer alignment occurs of aggregation process.Application of CaCO3 at a dose of 1,5, calculated by hydrolytic acidity, together with organic-mineral system of crops fertilizer allows to 47,7% transfer this process in macroaggregates. As a result - increase of deflationary stable aggregates contents  (diameter greater than 1 mm) to 58%. Keywords: the risk of deflation, agricultural land use, aggregate composition, chemical reclamation, fertilization system.